High-Frequency Soft-Switching PWM DC-DC Converter with Active Output Rectifier Operating as a Current Source for Arc Welding Applications. Issue 6 (3rd April 2017) - Dudrik, Jaroslav; Pástor, Marek; Lacko, Milan; Žatkovič, Róbert
Abstract: This paper introduces a high-frequency soft-switching pulse-width modulation DC-DC power converter with secondary active rectifier tested as a DC current source for arc welding applications. The soft-switching DC-DC converter consists of a high-frequency full-bridge inverter, high-frequency power transformer, and a controlled output rectifier with new secondary energy recovery turn-off snubber. Circulating currents in the converter are reduced by using active rectifier, and RMS values of the currents in primary and secondary switches are decreased by utilizing a novel control algorithm. The experimental results of a 4.5 kW DC-DC converter working at switching frequency of 100 kHz are presented.